2014
DOI: 10.1007/s11192-014-1486-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of academic collaboration in the impact of Latin-American research on management

Abstract: The aim of this paper is to determine the role that academic collaboration plays on the impact of Latin-American and the Caribbean research on management as an academic research discipline. The results show that the impact of Latin American articles on management, which were published between 1990 and 2010 in JCR journals is positively associated to collaboration r s = .133, p = .001. Collaborated articles have on average 1.22 times more impact than single authored ones. The level of collaboration is positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 60 publications
2
15
1
2
Order By: Relevance
“…This pattern is different from that reported for the impact of Latin American research on management [15] using the ISI Web of Science database. Forty-four countries shape the structure of the international collaboration network through the Journal of Theoretical and Applied Electronic Commerce Research.…”
Section: International Collaborationcontrasting
confidence: 99%
See 2 more Smart Citations
“…This pattern is different from that reported for the impact of Latin American research on management [15] using the ISI Web of Science database. Forty-four countries shape the structure of the international collaboration network through the Journal of Theoretical and Applied Electronic Commerce Research.…”
Section: International Collaborationcontrasting
confidence: 99%
“…Table 1). This result is similar to that reported for the network of Chinese scholars in management research [24] by using the ISI Web of Science database, but is different for the study that reported international collaboration for the discipline of management in Latin America [15].…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Although the findings reported in previous research show no agreement regarding the influence of academic collaboration on the impact of articles, scholars still believe that co‐authoring improves the quality of work and the probability of acceptance (Ronda‐Pupo, Díaz‐Contreras, Ronda‐Velázquez, & Ronda‐Pupo, ).…”
Section: Theory and Hypothesismentioning
confidence: 88%
“…() regarding the discipline of clinical and experimental cardiology and the study by Ronda‐Pupo et al. () addressing the field of management in Latin America.…”
Section: Methodsmentioning
confidence: 99%